Aktivitas Antibakteri Kombinasi Ekstrak Etanol Daun Johar (Cassia siemea Lamk) dan Daun Alpukat (Persea americana Mill) terhadap Streptococcus mutans - Taufik Turahman; Desi Purwaningsih (University Of Darussalam Gontor, 2022)
Dental caries is a dental infection with a high prevalence in Indonesia, one of the causes is Streptococcus mutans which demineralizes the tissues causing dissolution and dental caries. To reduce the number of microorganisms, people can utilize natural materials. One of the plants that have potential as an antibacterial is johar leaf and avocado leaf. The purpose of this study was to determine the antibacterial activity of the combination of ethanol extract of johar leaves (Cassia siamea Lamk) and avocado leaves (Persea americana Mill.) against Streptococcus mutans. This study uses the diffusion method. Extraction of johar leaves and avocado leaves was carried out by maceration method then the extracts were combined 1:1 with concentration series of 25%, 50%, 75% and 100%. Antibacterial testing uses the diffusion method to determine the inhibition. Streptococcus mutans bacteria were cultured at a density of 108 CFU/ml in MHA (Muller Hinton Agar) medium. Inhibitory power is known by measuring the diameter of the inhibition zone formed around the well. The average inhibition test results were obtained at concentrations of 25% (6 mm), 50% (6.1 mm), 75% (7.1 mm) and 100% (9.3 mm). The positive control of ciprofloxacin (30 mm) and the negative control did not show the diameter of the inhibition zone. So that the greater the concentration of the extract combination, the greater the diameter of the inhibition zone obtained to inhibit the growth of Streptococcus mutans and there is a significant difference in the diameter of the inhibition zone of the combination of extracts and ciprofloxacin positive control.